Effect of mass medication on the health and gain of calves in grass paddocks or feedlot pens - Brazle, F.K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Four hundred and ninety mixed-breed, long-hauled, bull calves averaging 275 lb were used in a winter study to determine whether mass medicating calves in grass paddocks or feedlot pens would reduce health problems and improve performance. All calves were started in feedlot pens for 3 days, then half of the calves were turned out into grass paddocks. Mass medication with injectable oxytetracycline did not improve health or gain of the calves. Calves housed in grass paddocks during the recurring period had less sickness (P<.01), fewer (P<.05) sick days per animal purchased, and lower (P<.05) drug treatment costs than their counterparts housed in feedlot pens.
Keywords: Beef; Feedlot pens; Grass paddocks; Performance